Acetate-based Ionic Liquid in Oil Microemulsion as a Carrier for Acyclovir and Methotrexate - KANDASAMY, SHALINI (2019)
Transdermal Drug Delivery (TDD) is an alternative drug administration technology to oral delivery and hypodermal injections as they are regarded as safe and non-invasive. Recently, Ionic Liquid-in-oil microemulsions (IL/O MEs) have emerged as a potential carrier for TDD.